Are sustainability-linked loans designed to effectively incentivize corporate sustainability? A framework for review - Alix Auzepy; Christina E. Bannier; Fabio Martin (Financial Management, 2023)
This paper analyzes sustainability-linked loans (SLLs), a new category of debt instrument that incorporates environmental, social, and governance (ESG) considerations. Using a large sample of loans issued between 2017 and 2022, we assess the design of SLLs by evaluating their key performance indicators (KPIs) using a comprehensive quality score. Our findings suggest that SLLs only partially rely on KPIs that generate credible sustainability incentives. We document that SLL borrowers do not significantly improve their ESG performance post issuance and show that stock markets are rather indifferent to the issuance of SLLs by EU borrowers, while SLL issuance announcements by US borrowers are met with significantly negative abnormal returns by investors. These findings call into question the beneficial sustainability and signaling effects that borrowers may hope to achieve by issuing ESG-linked~debt.
Keywords: 650; ESG-linked loans; sustainability KPIs; sustainability-linked loans